The effect of the blended Problem-Based Learning method on the acquisition of content-specific knowledge in mechanical engineering - Alias, Maizam (World Institute for Engineering and Technology Education, 2007)
Problem-Based Learning (PBL) on its own has not been very successful in ensuring the learning of content-specific knowledge in engineering. The purpose of this study was to determine the effect of blending PBL and conventional teaching methods on students' achievements in mechanical engineering. The quasi-experimental design method was used with two classes of first year mechanical engineering students who registered for the Fluid Mechanics I course at Tun Hussein Onn University of Malaysia in Johor Darul Takzim, Malaysia. The experimental group («=28) was prescribed the blended PBL method while the control group (n=52) used the conventional method for completing group tasks. A pre-test and two post-tests on selected topics in Fluid Mechanics / were administered to both groups before the study in weeks 4 and 11, respectively. The results showed that the mean scores on the achievement tests of the blended PBL group was statistically significantly higher than the conventional group in both instances (weeks 4 and 11) with the effect sizes ranging from 0.56 to 1.1. It was concluded that blended PBL is better at developing content-specific knowledge compared to the conventional method.